Discrimination of turmeric from different origins in China by MRM-based curcuminoid profiling and multivariate analysis. (15th February 2021) - Jia, Shuailong; Sun, Yi; Li, Lieyao; Wang, Runjing; Xiang, Yi; Li, Sen; Zhang, Yang; Jiang, Hongliang; Du, Zhifeng
Highlights: RSM was applied for optimizing the extraction process of minor curcuminoids. MRM parameters including DP and CE for each curcuminoid were optimized. The established method could discriminate turmeric samples from different origins. This study was useful for discriminating other geo-authentic and non-authentic herbs. Abstract: In this research, a three-step strategy was utilized for discriminating turmeric samples from different provinces and regions in China. Firstly, MRM-based UPLC-MS/MS method for chemical profiling of curcuminoids in turmeric samples was established. Then, response surface methodology was applied for optimizing the extraction process of targeted curcuminoids. Finally, multivariate analysis was conducted for systematic characterization of 66 curcuminoids in turmeric. Principal component analysis (PCA) and orthogonal projection to latent structure-discriminant analysis (OPLS-DA) revealed that turmeric samples from Sichuan and other regions could be classified into two distinct groups. Turmeric samples from the same group had similar curcuminoids content distribution. 25 differential curcuminoids were discovered through OPLS-DA, among which most curcuminoids were more abundant in Sichuan. Furthermore, turmeric samples from different provinces could be clearly discriminated based on hierarchical cluster analysis (HCA) using the screened differential curcuminoids.